PEMBERLAKUAN KEMBALI DELIK PENGHINAAN PRESIDEN/WAKIL PRESIDEN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 013-022/PUU-IV/2006 - Gilang Abi Zaifa (2023)
The reinstatement of the article regarding insulting the President and/or Vice President in the Criminal Code has only received special attention from the public. This is because the article has been annulled by the Constitutional Court through the Constitutional Court's decision Number 013-022/PUU-IV/2006. In this decision, the judges of the Constitutional Court ruled that the article on insulting the President and/or Vice President does not have a binding law because it is against the constitution. In this decision the judges of the Constitutional Court also argued that similar or the same articles may not be re-incorporated into the Criminal Code. Based on these problems, the author draws a formulation of the problem that will be studied in this writing, namely, 1) What is the reason for the government to reinstate the article on insulting the President and/or Vice President in the new Criminal Code? and 2) Constitutionalism of the article on insulting the President and/or vice president in the new Criminal Code. At this writing the research method used is normative legal research, legal research conducted by examining literature or secondary data. The approach used is the Legislative Approach (statue approach) and conceptual approach(conceptual approach). In the discussion of this writing. The government's reasons for reinstating these articles are to protect the honor, dignity and dignity of a President/Vice President and also the government thinks that the offense in the article on insulting the President/Vice President in the latest Criminal Code is different from the offense that was canceled by the Constitutional Court. The article on insulting the President/Vice President contained in Articles 218-220 of the newest Criminal Code is also unconstitutional. This is because the article can silence people's freedom to express opinions both orally and in writing. The article on insulting the President/Vice President in the latest Criminal Code contradicts Article 28, Article 28E and Article 28F of the 1945 Constitution of the Republic of Indonesia.